A new species of Anolis (Squamata: Iguania: Dactyloidae) formerly referred to as A. pachypus from the Cordillera de Talamanca of western Panama and adjacent Costa Rica - Lotzkat, Sebastian; Bienentreu, Joe-Felix; Hertz, Andreas; Köhler, Gunther (Zootaxa, 2011)
We describe Anolis benedikti sp. nov. from lower montane elevations of the Cordillera de Talamanca in Bocas del Toro and Chiriquí provinces of western Panama, and adjacent Puntarenas province of eastern Costa Rica. The new species is very similar to A. magnaphallus, A. pachypus, A. pseudopachypus, and A. tropidolepis, which inhabit the same mountain range. It differs from these species in the coloration of the male dewlap, which is red with a yellow anterior margin (versus male dewlap solid purplish red in A. magnaphallus and A. tropidolepis, red with a central yellow blotch in A. pachypus, and solid yellow in A. pseudopachypus), and in pholidotic characters.